Compact Stretcher with Shock Absorbers : A Proposed Model - Waghmare, S. N.; Sawant, N. A.; Dhumal, S. D.; Patil, P. G.; Kedar, N. T. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2014)
Stretcher is an essential part of medical first aid system. Safe and early delivery can save life of a serious patient. Today stretcher is available in different designs. Efforts are taken to make the stretcher more comfortable in ergonomic point of view and more attractive in aesthetic point of view. Use of shock absorber in hand lifting stretcher helps not only to reduce shocks produced due to rough travelling and natural calamities but also reduces chances of bleeding and damage to internal body parts due to shocks or vibrations generated during fast and rough travelling. The paper proposes a model of compact stretcher with shock absorbers and also discusses the way for analysis of the stretcher.